A complementaridade dos possessivos e das construções genitivas no português coloquial: Réplica a Perini (1985) - Kato, Mary A. (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
Perini (this volume) analyses the uneven distribution of possessives in Brazilian coloquial Portuguese and postulates some functional principles to account for it, My claim in this paper is that the facts analysed by the author as a grammatical problem should be viewed as matter of use. The principles proposed in the article should not therefore be treated as constraints on the form of grammar but rather as restrictions on its output.